# (4-v)(4v+3)=0

## Simple and best practice solution for (4-v)(4v+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (4-v)(4v+3)=0 equation:

Simplifying
(4 + -1v)(4v + 3) = 0
Reorder the terms:
(4 + -1v)(3 + 4v) = 0
Multiply (4 + -1v) * (3 + 4v)
(4(3 + 4v) + -1v * (3 + 4v)) = 0
((3 * 4 + 4v * 4) + -1v * (3 + 4v)) = 0
((12 + 16v) + -1v * (3 + 4v)) = 0
(12 + 16v + (3 * -1v + 4v * -1v)) = 0
(12 + 16v + (-3v + -4v2)) = 0
Combine like terms: 16v + -3v = 13v
(12 + 13v + -4v2) = 0
Solving
12 + 13v + -4v2 = 0
Solving for variable 'v'.
Factor a trinomial.
(4 + -1v)(3 + 4v) = 0

#### Subproblem 1

Set the factor '(4 + -1v)' equal to zero and attempt to solve: Simplifying 4 + -1v = 0 Solving 4 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1v = 0 + -4 -1v = 0 + -4 Combine like terms: 0 + -4 = -4 -1v = -4 Divide each side by '-1'. v = 4 Simplifying v = 4

#### Subproblem 2

Set the factor '(3 + 4v)' equal to zero and attempt to solve: Simplifying 3 + 4v = 0 Solving 3 + 4v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4v = 0 + -3 4v = 0 + -3 Combine like terms: 0 + -3 = -3 4v = -3 Divide each side by '4'. v = -0.75 Simplifying v = -0.75

v = {4, -0.75}